Analysis of machining characteristics in electrical discharge machining of SiC and Al2O3 reinforced AA6061 hybrid metal matrix composites using Taguchi and ANOVA techniques. (1st April 2022) - Haja Syeddu Masooth, P; Bharathiraja, G; Jayakumar, V; Palani, Kumaran
Abstract: In this study, the machining behaviour of aluminium alloy (AA6061)/10% aluminium oxide (Al2 O3 )/10% silicon carbide (SiC) hybrid metal matrix composites was analyzed by Electric Discharge Machining (EDM). The stir casting method was used to fabricate the composite in a volume percentage of 80, 10, and 10 for AA6061, Al2 O3 and SiC, respectively. The specimen was prepared in the size of 30 mm in diameter and 12 mm in thickness from the fabricated composite by the Wire-cut Electric Discharge Machining (WEDM) process. The fabricated specimens were machined using EDM by varying the input parameters of pulse-ON time (T–ON) in μ s, pulse-OFF time (T–OFF) in μ s, and gap current (GC) in amps at three different levels. The design of the experiment by the Taguchi method was used with the L9 orthogonal array. The impact of process parameters on output variables such as Surface Roughness (SR), Machining Time (MT) and Material Removal Rate (MRR) was studied, and an Analysis of Variance (ANOVA) was carried out to identify the most influencing parameter. The GC is observed as the significant input parameter on SR and MT as the percentage contribution of 33% and 47%, respectively. T–ON is identified as more significant than other parameters on MRR as the percentage contribution is 47%. The results show that T–ON time of 12 μ s, T–OFF time of 4 μ s, and GC of 14 amps yield the least value of 3.304 μ m for SR, 12 min for MT, and a higher value of 0.037 mm 3 min −1 for MRR.